Polymorphism and sodium-ion conductivity of NaTa2PO8 synthesized via the Li+/Na+ ion-exchange reaction of LiTa2PO8 - Kim, Jaegyeom; Ha, Junho; Khefif, Fouzia; Kim, Jong Young; Pee, Jae Hwan; Kim, Seung Joo (Ceramics International, 2022)
Ion exchange reaction is a promising method to explore metastable compounds that could not be synthesized by conventional high-temperature solid-phase reactions. Herein, a new sodium tantalum phosphate, NaTa2PO8 was synthesized via the Li+/Na+ ion-exchange reaction of the parent compound, LiTa2PO8 in molten NaNO3 medium. NaTa2PO8 underwent an irreversible phase transition from the low- (LT-NaTa2PO8) to the high-temperature polymorph (HT-NaTa2PO8) at approximately 1000 °C. The crystal structures were solved using an ab initio structural determination method based on synchrotron X-ray powder diffraction data. The LT-NaTa2PO8 presented an orthorhombic structure, closely related to that of the parent LiTa2PO8 structure. In contrast, the HT-NaTa2PO8 was found to adopt a monoclinic structure, belonging to a family of monophosphate tungsten bronzes with pentagonal tunnels. The ionic conductivities of LT-NaTa2PO8 (σ = 5 × 10−5 S/cm at 309 °C) and HT-NaTa2PO8 (σ = 2 × 10−7 S/cm at 300 °C) exhibited Arrhenius behavior with activation energies of 0.49 and 0.79 eV, respectively. Bond valence energy landscape (BVEL) calculations indicated that a three-dimensional (3D) conduction pathway is formed in LT-NaTa2PO8 structure, while the conduction pathway in HT-NaTa2PO8 shows a two-dimensional (2D) character.
Keywords: High temperature solid phase reaction; Ion conductivities; Ion exchange reactions; Li +; Metastable compounds; Na+ ions; Parent compounds; Sodium ions; Synthesised; X- ray diffractions; Ion-exchange; Ionic conductivity; Polymorphism; X-ray diffraction